Stress induced a shift from dorsal hippocampus to prefrontal cortex dependent memory retrieval: role of regional corticosterone - Dominguez, Gaelle; Faucher, Pierre; Henkous, Nadia; Krazem, Ali; Piérard, Christophe; Béracochéa, Daniel (Frontiers in Behavioral Neuroscience, 2014)
Most of the deleterious effects of stress on memory retrieval are due to a dysfunction of the hippocampo-prefrontal cortex interplay. The role of the stress-induced regional corticosterone increase in such dysfunction remains however unclear, since there is no published study as yet dedicated to measuring corticosterone concentrations simultaneously in both the prefrontal cortex (mPFC) and the hippocampus (dHPC) in relation with memory impairments. To that aim, we first showed in Experiment 1 that an acute stress (3 electric footschocks; 0.9 mA each) delivered before memory testing reversed the memory retrieval pattern (MRP) in a serial discrimination task in which mice learned two successive discriminations. More precisely, whereas non-stressed animals remembered accurately the first learned discrimination and not the second one, stressed mice remembered more accurately the second discrimination but not the first one. We demonstrated that local inactivation of dHPC or mPFC with the anesthetic lidocaine recruited the dHPC activity in non-stress conditions whereas the stress-induced MRP inversion recruited the mPFC activity. In a second experiment, we showed that acute stress induced a very similar time-course evolution of corticosterone rises within both the mPFC and dHPC. In a 3rd experiment, we found however that in situ injections of corticosterone either within the mPFC or the dHPC before memory testing favored the emergence of the mPFC-dependent MRP but blocked the emergence of the dHPC-dependent one. Overall, our study evidences that the simultaneous increase of corticosterone after stress in both areas induces a shift from dHPC (non stress condition) to mPFC-dependent memory retrieval pattern and that corticosterone is critically involved in mediating the deleterious effects of stress on cognitive functions involving the mPFC-HPC interplay.